Technology Impacts on Moral Development ES Students - Susanti, Marnis; Desyandri, Desyandri; Irdamurni, Irdamurni (International Journal of Educational Dynamics, 2023)
The development of Information and Communication Technology (ICT) at this time has many impacts on people's lives, especially for Elementary School (ES) students, both positive and negative impacts. This study aims to determine the impact of ICT on the moral development of ES students. The method used in this research is qualitative with interview, observation, and documentation techniques. The research subjects were 6th-grade ES students. Analysis of the research data was carried out using a qualitative descriptive analysis. The results of the study show that most of the users of ICT without parental and teacher control have a great impact on student development. The negative impacts are that students are lazy to learn, ignorant, lack discipline, impolite behavior appears, and changes in social interaction, and dependence on Android. The teacher's efforts to overcome this are through digital literacy education, monitoring and limiting the use of technology, selecting quality content, discussion and reflection, collaboration with parents, and being a model of good behavior. With holistic education, ES students can gain understanding and strong moral skills that will help them become responsible, ethical, and contributing individuals in society.